Reviewers - Psicología, Actualidades (2019)
David Jimenez Rodriguez, Universidad Autónoma del Estado de Hidalgo, México Horacio García, Universidad Nacional de San Luis, Argentina Fabiola Gonzalez-Betanzos, Universidad Michoacana de San Nicolás de Hidalgo, México Eugenia Razumiejczyk, Universidad Nacional de Entre Ríos, Argentina José Arana, Universidad de Salamanca, España Ludgleydson Fernandes de Araújo, Universidade Federal do Piauí, Brasil Rebecca Lemos Igreja, Universidade de Brasília, Brasil Josefa Ruiz Romero, Universidad de Granada, España Laura Torres Velázquez, Universidad Nacional Autónoma de México, México Gloriana Rodríguez Arauz, Universidad de Costa Rica, Costa Rica Mónica Roncancio, Universidad Pontificia Bolivariana, Colombia Ana Betina Lacunza, Universidad Católica de Salta, Argentina José Rondón Bernard, Universidad Central de Venezuela, Venezuela Graciela Ordoñez, Universidad de Costa Rica, Costa Rica Sonia Romero Espino, Universidad a Distancia de Madrid, España Inês Carvalho Relva, University of Trás-os-Montes and alto Douro, Portugal Márcia Jager, Universidade Regional Integrada do Alto Uruguai e das Missões, Brasil María Londoño Londoño, Centro de Investigación en Comportamiento Organizacional, Colombia Maribel Giraldo Isaza, Centro de Investigación en Comportamiento Organizacional, Colombia